1994
DOI: 10.1111/j.1600-0714.1994.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cellular and nuclear volumetric alterations in epithelium from lichen planus lesions of human buccal mucosa

Abstract: Patients with oral lichen planus lesions may represent a relatively high risk population for subsequent development of oral cancer. Little is known of the relative effects of chronic inflammation and the process of malignant transformation itself on the histological structure of transforming epithelia. We have assessed cellular and nuclear volumes in defined basal and spinous cells from normal buccal mucosa epithelium, from epithelium associated with a non-specific chronic inflammatory infiltrate and from lich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
(21 reference statements)
0
5
0
4
Order By: Relevance
“…Although several molecular biologic markers have been suggested to be useful as an additional diagnostic tool in diagnosing OLP, there seems not to be enough scientific evidence yet to apply those as a ‘golden standard’(9–13). Direct immunofluorescent techniques have also been described as additional tool in the diagnostic assessment of OLP (14–20).…”
Section: Discussionmentioning
confidence: 99%
“…Although several molecular biologic markers have been suggested to be useful as an additional diagnostic tool in diagnosing OLP, there seems not to be enough scientific evidence yet to apply those as a ‘golden standard’(9–13). Direct immunofluorescent techniques have also been described as additional tool in the diagnostic assessment of OLP (14–20).…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few studies which we compare our findings with (8,9,26) there is little morphometric information in the literature. Previous quantitative studies have dealt with different aspects of the disease and have utilized other parameters.…”
Section: Discussionmentioning
confidence: 87%
“…These results suggest that oral LL may represent a nonspecific inflammatory stomatitis which possess a lichenoid appearance, and hence do not behave the same way as oral LPs. White et al (8) when comparing normal tissues with nonspecific inflammatory mucosal lesions noted no differences between these two groups. In contrast, they showed that significant differences were present when normal tissues were compared to oral LP and when nonspecific inflammatory lesions were compared to oral LP.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The diagnoses were made independently by three authors (YJ; LY and FHW). The criteria for diagnosis were based on previous publications [2,16,29].…”
Section: Methodsmentioning
confidence: 99%